BIG DATA AND METAVERSE TOWARD BUSINESS OPERATIONS IN INDONESIA - Depari, Genesis Sembiring; Efin Shu; Indra, Indra (SEAN Institute, 2022)
The rapid growth of information and technology recently brings new opportunities in business operational. An optimal used of resources may leads into business efficiency and therefore minimizing operational cost. Moreover, new opportunities are also revealed by creating more innovations in business. Metaverse gain its popular name firstly in public awareness in October 2021, when Facebook, Inc. renamed it